Cowpea mosaic virus VPg: sequencing of radiochemically modified protein allows mapping of the gene on B RNA - Zabel, Pim (1984)
A partial amino acid sequence of cowpea mosaic virus (CPMV) VPg radiochemically modified by chloramine-T and Bolton-Hunter reagent has been determined. VPg covalently bound to viral RNA chains (VPg-RNA) was iodinated with chloramine-T and Bolton-Hunter reagent to label tyrosine and lysine residues, respectively. [(125)I]VPg-RNA was digested with nuclease P1 and the resulting [(125)I]VPg-pU was purified by SDS-polyacrylamide gel electrophoresis and subjected to automated Edman degradation. Control experiments with chemically synthesized poliovirus VPg showed the feasibility of radiochemical microsequence analysis of protein that had been radiochemically modified by chloramine-T and Bolton-Hunter reagent. Analysis of CPMV [(125)I]VPg-pU revealed the presence of tyrosine residues at position 12 and 14, and of lysine residues at position 3 and 20, respectively. In combination with Edman degradation of unlabeled CPMV VPg, which showed serine and arginine residues to be present at position 1 and 2, respectively, the data obtained allow the precise positioning of VPg within the 200 000 dalton (200 K) polyprotein encoded by CPMV B RNA and the prediction of its entire amino acid sequence. VPg is located at the COOH terminus of its 60 K, membrane-bound,precursor and proximal to the amino terminus of the protease-polymerase domain of the polyprotein. A processing scheme for the 200 K polyprotein is discussed in which Gln-Ser amino acid pairs act as the major signal for proteolytic cleavage.